The Integration of Pesantren and Madrasah Curriculum and Its Implication on Students' Academic Achievement (Sekolah Tinggi Agama Islam Ma'had Ali Cirebon, 2023)
This study aimed to determine the form of integration of the pesantren (Boarding School) and madrasah Aliyah (Islamic High School) curriculum and its implications for student academic achievement at Madrasah Aliyah (MA) Nahdlatul Ulama (NU) Assalafie Babakan Ciwaringin Cirebon. This study used descriptive qualitative with field research, while in data collection techniques of the study used observation, interview and documentation methods. While the data analysis technique used the Milles and Huberman model, that was data reduction, data presentation and conclusions. The integration of curriculum was a combination, harmony coordination, completeness so that it became a unified whole. Each educational institution had a draft educational plan that was adjusted by the central Education Office, but not all educational institutions had the same style of education, especially as in an Islamic boarding school-based educational institution whose educational style combined Islamic boarding school-based education with public school education. The form of integration of the pesantren and madrasahcurriculum at MA NU Assalafie includes: first, integration of pesantren and madrasah curriculum implementation programs. Second, incorporate pesantren subjects into the Madrasah curriculum. Third, integration in choosing teaching materials. Fourth, incorporating religious and Islamic values. Fifth, integration of supervision of the implementation of Pesantren and Madrasah curriculum. The implications of integrating the curriculum of pesantren and madrasah had a positive influence. This could be seen from the results of the learning scores obtained by students, the average student learning outcomes above the Minimum Completeness Criteria or Kriteria Ketuntasan Minimal (KKM) score.